Pola Pernikahan Asortatif dan Ketimpangan Pengeluaran Penduduk di Jawa Barat - Kristy, Nurine (Seminar Nasional Official Statistics, 2024)
West Java is one of the provinces with the largest population in Indonesia. West Java's economic in 2023 was 5.05 percent, but the economic gap increases continuesly every year. Assortative mating, especially education, are indicated to have contributed to widening the gap in society. This study aims to analyze assortative mating, both in terms of age and education in West Java in 2022. This study also analyzes the relationship between assortative mating and per capita expenditure inequality. Graphs, tables, Kendall's Tau correlation, and the Lorenz curve were used in this study. This study use data from Susenas, March 2022. The results of the analysis showed that education assortative mating occurred in West Java. The marriage pattern that occurred was positive assortative mating in all regional categories. The relationship between assortative mating and per capita expenditure inequality is that there is an indication that assortative mating has an association with per capita expenditure inequality that is getting worse (more unequal).